Reputation Risk Management in Islamic Banking in Indonesia - Dodi Eka Nugraha (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
Inherent risk is the risk inherent in the business activities of islamic banks, both of which can dikuantiflkasikan or not, which could potentially affect the financial position of the bank risk management, particularly reputational risk for the islamic banks, either individually or for banks in consolidation with the subsidiaries most involved the active supervision of the board of commissioners, directors, and DPS, policies, procedures, and limits, and the process of identification, measurement, monitoring, and control of the risk and SIM risk. The risk of this arising, mostly because of the media coverage and rumors about the banks that are negative as well as the communication strategy of the bank are less effective. The negative publicity against one of the islamic banks would contaminate the reputation of the bank the islamic other, although islamic banks other not to engage in responsible action. How to control reputation risk is best with the anticipation/preventive action and maintenance program reputation. Reputation risk is a risk which is abstract and shaped the intangible asset for the company. The handling of reputation risk should be preventive because of the cost of the completion of this risk is large and as a result can damage and kill the company